Molecular and serological diagnosis of hepatitis e virus in swine and chicken - Priscilla Freitas Gerber (2014)
Hepatitis E virus (HEV) has been identified in several animal species. Based on the host tropism the strains can be clustered into mammalian HEV (mHEV), avian HEV (aHEV), and in piscine HEV strains. The aim of the first study was to compare the performance of two single-plex reverse transcriptase (RT)-PCR assays for broad detection of all four mHEV genotypes (assays A and B) and two duplex RT-PCR assays for detection and differentiation of mHEV-3 and -4 (assay C and D). RNA extracted from 28 fecal samples from pigs experimentally inoculated with HEV-3 and 186 fecal samples from commercial pigs with unknown HEV exposure were tested. For assays A, B, C and D HEV RNA was detected respectively in 96.4%, 39.2%, 14.2%, and 0% of the experimental samples, and in 67.2%, 36.4%, 1.1%, and 0.5% of the field samples. Assays showed an overall poor agreement. Assays A and B had higher detection rates for HEV RNA than assays C and D (p < 0.05). In the second study, 40 fecal samples were collected from pigs at 7, 10, 13 or 17 weeks of age in 10 farms. Twenty nine (72.5%) samples tested positive for HEV RNA by RT-PCR. All 10 farms had at least one positive sample. All six yield sequences clustered in genotype 3. In the third study, 160 serum samples from chicken ranging from six to 118-weeks of age were collected on three farms and tested for aHEV antibodies by a fluorescent microbead-based assay. Anti-aHEV IgY were detected in 17% of the chickens. Forty pooled fecal samples from eight farms were tested for aHEV RNA by RT-PCR and three (8%) were positive for the helicase gene. This work provides evidence of circulation of aHEV in the Brazilian chicken population.